Supply Chain Management Performance in Tourism. Continental Hotels Chain Case - Gabriela Ţigu; Bogdan Călăreţu (Amfiteatru Economic Journal, 2013)
With its origins in logistics, Supply Chain Management (SCM) concept is covering all managerial aspects of the flow of materials and information from source to customer, across the entire range of materials handling and movement functions, and throughout an organization and its supply channels. In tourism, these issues relate to the whole process of providing tourism services from sourcing of raw materials, products or different services) to supply and distribution, and SCM performance can ultimately be measured by customer satisfaction. Thus, an important component of tourism SCM is the demand management. Therefore, this study aims to highlight the features of the concept of SCM and demand management in tourism, with an emphasis on a hotel chain in Romania, based on research and analysis of tourist traffic indicators as well as assessment of customers satisfaction. The sources of information are the internal company statistics, as well as various hotels booking websites that offer customers' feedback. The results of the study provide a snapshot of how the hotel demand management can influence SCM performance in tourism.
Keywords: L83; M10; 330; Supply chain management; demand management; hotel services; distributions strategies; tourist traffic indicators